2019
DOI: 10.3847/1538-4357/ab4a0e
|View full text |Cite
|
Sign up to set email alerts
|

A New Measurement of the Hubble Constant and Matter Content of the Universe Using Extragalactic Background Light γ-Ray Attenuation

Abstract: The Hubble constant H 0 and matter density Ω m of the Universe are measured using the latest γray attenuation results from Fermi-LAT and Cherenkov telescopes. This methodology is based upon the fact that the extragalactic background light supplies opacity for very high energy photons via photon-photon interaction. The amount of γ-ray attenuation along the line of sight depends on the expansion rate and matter content of the Universe. This novel strategy results in a value of H 0 = 67.4 +6.0 −6.2 km s −1 Mpc −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 88 publications
(87 reference statements)
9
66
0
Order By: Relevance
“…Complementary constraints of cosmological parameters, such as H 0 and Ω M , can also be expected from this observation program. The γ-ray optical depth is to first order proportional to the EBL density and inversely proportional to H 0 [15,[80][81][82][83]. As a result, for an EBL spectrum fixed to the level expected from galaxy counts, the uncertainty on H 0 is at least as great as the uncertainty on the scale factor α.…”
Section: Determination Of the Optical Depthmentioning
confidence: 98%
See 1 more Smart Citation
“…Complementary constraints of cosmological parameters, such as H 0 and Ω M , can also be expected from this observation program. The γ-ray optical depth is to first order proportional to the EBL density and inversely proportional to H 0 [15,[80][81][82][83]. As a result, for an EBL spectrum fixed to the level expected from galaxy counts, the uncertainty on H 0 is at least as great as the uncertainty on the scale factor α.…”
Section: Determination Of the Optical Depthmentioning
confidence: 98%
“…These results will also enable an estimation of the cosmic star-formation history (see Refs. [22,202]) and enable an independent determination of cosmological parameters [83]. Sensitivity studies dedicated to these more specific topics shall be conducted in the future.…”
Section: Perspectives On Cta Constraints Of γ-Ray Propagationmentioning
confidence: 99%
“…Our Abbott et al 2018) are shown at the bottom. The next is an estimate using extragalactic background light γ ray attenuation (Domínguez et al 2019) and another from BAO at all redshifts + BBN estimate (Cuceu et al 2019). Then we show measurements from SNe Ia calibrated with TRGB (Freedman et al 2019), SNe Ia calibrated with Cepheids (SH0ES sample, Riess et al 2016Riess et al , 2019, using near-infrared (NIR) filters (Burns et al 2018) and SNe Ia with Mira variables (Huang et al 2020).…”
Section: Hubble Tensionmentioning
confidence: 99%
“…The Hubble constant H0 is estimated to be about 70 km/Mpc. Recent observations report, for example, 68 km/sMpc [8] and 74 km/sMpc [9]. This value is a universal value for all photons.…”
Section: Large Number Ratiosmentioning
confidence: 77%